Pemanfaatan Buah Mangrove Menjadi Kopi Mangrove di Kecamatan Anggrek Kabupaten Gorontalo Utara - Wahyudin Hasan; Afdal S. Hatta; Gamar Sri Wahyuningsi Winowoda; Moh Rizal A. Pontoh; Aditya Putri Mayasari Pakaya; Fransiska Nteseo; Nurindah Thalib; Yulinda Djalilu; Zulkifli Pakaya; Ryan Ishak; Rachelia Porogoi (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
Mangrove forests have a high value for the lives of coastal communities. Efforts to utilize the mangrove forest certainly need adequate knowledge so that the sustainability and existence of the mangrove forest is maintained. The purpose of this activity is to educate and provide knowledge to the community about utilizing mangrove fruit in mangrove coffee. The method used is to present theories about the stages of making mangrove coffee and direct questions and answers. From the implementation of the activity, it was found that the participants gained an understanding of processing mangrove fruit into mangrove coffee. It is hoped that this product will become an added value for the community around the coast in the Anggrek District, North Gorontalo Regency.Hutan mangrove memiliki nilai manfaat yang tinggi bagi kehidupan masyarakat pesisir. Upaya pemanfaatan ekosistem hutan mangrove tersebut tentu perlu pengetahuan yang memadai agar kelestarian dan keberadaan hutan mangrove tetap terjaga. Tujuan penyelenggaraan kegiatan ini untuk mengedukasi dan memberikan pengetahuan kepada masyarakat dalam memanfaatkan buah mangrove menjadi kopi mangrove. Metode yang digunakan yakni pemberian teori tentang tahapan pembuatan kopi mangrove serta tanya jawab langsung. Dari pelaksanaan kegiatan diperoleh hasil bahwa peserta memperoleh pemahaman tentang pengolahan buah mangrove menjadi kopi mangrove. Diharapkan produk ini menjadi nilai tambah bagi masyarakat sekitar pesisir pantai di Kecamatan Anggrek Kabupaten Gorontalo Utara.